2020
DOI: 10.1002/hep.31042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol Use Disorder Treatment on Clinical Outcomes Among Patients With Cirrhosis

Abstract: BaCKgRoUND aND aIMS:Despite the significant medical and economic consequences of coexisting alcohol use disorder (AUD) in patients with cirrhosis, little is known about AUD treatment patterns and their impact on clinical outcomes in this population. We aimed to characterize the use of and outcomes associated with AUD treatment in patients with cirrhosis. appRoaCH aND ReSUltS: This retrospective cohort study included Veterans with cirrhosis who received Veterans Health Administration care and had an index diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
174
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(183 citation statements)
references
References 48 publications
8
174
1
Order By: Relevance
“…A recent Veteran Affairs healthcare system study highlighted the extent of this deficiency, reporting that only 0.4% of AUD patients received pharmacotherapy alone and 1% received both behavioral and pharmacotherapy over a 180-day period after initial diagnosis. 17 Importantly, in this study, pharmacotherapy-based AUD treatment alone (versus no AUD treatment) was associated with a significant reduction in incident hepatic decompensation (5.5% versus 11.6%) and in mortality (0.6% versus 3.9%). 17 Further studies are needed to confirm this mortality benefit.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…A recent Veteran Affairs healthcare system study highlighted the extent of this deficiency, reporting that only 0.4% of AUD patients received pharmacotherapy alone and 1% received both behavioral and pharmacotherapy over a 180-day period after initial diagnosis. 17 Importantly, in this study, pharmacotherapy-based AUD treatment alone (versus no AUD treatment) was associated with a significant reduction in incident hepatic decompensation (5.5% versus 11.6%) and in mortality (0.6% versus 3.9%). 17 Further studies are needed to confirm this mortality benefit.…”
Section: Introductionmentioning
confidence: 57%
“… 17 Importantly, in this study, pharmacotherapy-based AUD treatment alone (versus no AUD treatment) was associated with a significant reduction in incident hepatic decompensation (5.5% versus 11.6%) and in mortality (0.6% versus 3.9%). 17 Further studies are needed to confirm this mortality benefit. The reasons for underutilization of AUD pharmacotherapy appear multifactorial, with a significant factor undoubtedly being the shortage of addiction specialist physicians in the United States.…”
Section: Introductionmentioning
confidence: 57%
“…However, we take hope from two papers in this issue of Hepatology that point to the future for better care for patients with ALD. ( 6,7 ) In the first study, Preoschold‐Bell et al compared Screening, Brief Intervention, and Referral to Treatment (SBIRT) with SBIRT and enhanced treatment of AUD, with an aim to reduce alcohol consumption in patients with hepatitis C virus (HCV) infection. ( 7 ) Subjects attending three out‐patient clinics from October 2014 to September 2017 were identified as candidates for the study using the AUD Identification Test questionnaire.…”
Section: Figmentioning
confidence: 99%
“…The study by Rogal et al provides a fascinating retrospective account of treatments of AUD in patients with cirrhosis in the U.S. Veterans Affairs (VA) integrated health system. ( 6 ) Among a cohort of almost 100,000 subjects with cirrhosis, 35,682 were identified with a new diagnosis of AUD. The authors showed that only 14% received treatment for AUD within 180 days of the index diagnosis of AUD, with 12% receiving behavioral therapy alone, 0.4% pharmacotherapy alone, and 1% both behavioral and pharmacotherapy.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation